1983
DOI: 10.1159/000260692
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Artificial Caries-Like Lesions by Quantitative Microradiography and Microhardness Profiles

Abstract: A direct comparison of quantitative microradiography and microhardness profiles was made using artificial caries-like lesions in human enamel. Tooth crowns with lesions were cut in half through the center of the lesions and opposing halves were assessed by one of the techniques, from the anatomical surface, across the lesion, and into the underlying enamel. A linear relationship was found between volume percent mineral determined by microradiography and the square root of the Knoop Hardness Number assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
334
5
47

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(405 citation statements)
references
References 6 publications
19
334
5
47
Order By: Relevance
“…At the pre-beverage intake stage, both in human and bovine enamel, the Knoop hardness amounted to some 420 KHN, values slightly higher than those previously reported (17,18), which may be attributed to the fact that the enamel outer surface was only minimally removed during specimen preparation. In effect, it has already been demonstrated that microhardness of enamel varies with depth (18).…”
Section: Discussioncontrasting
confidence: 54%
“…At the pre-beverage intake stage, both in human and bovine enamel, the Knoop hardness amounted to some 420 KHN, values slightly higher than those previously reported (17,18), which may be attributed to the fact that the enamel outer surface was only minimally removed during specimen preparation. In effect, it has already been demonstrated that microhardness of enamel varies with depth (18).…”
Section: Discussioncontrasting
confidence: 54%
“…% min.) 17 and the area of mineral loss (∆Z) for each treatment was calculated by numerical integration using the trapezoidal rule.…”
Section: Surface Hardness Analysismentioning
confidence: 99%
“…The amount of iodide recovered in the discs is determined and provides information about the pore volume of the enamel. It was shown that (IPT) measurements are closely related to the pore [26] showed that exposure to acidic drinks leads to an increase in IP which was significantly associated with the acidity, pH, and min-eral contents of the drinks. In contrast to the aforementioned study, Lussi et al [28] [26] found a correlation between IP and microhardness data for enamel samples immersed in acidic beverages for a period of 20 min.…”
Section: Iodide Permeability Testmentioning
confidence: 99%
“…Nevertheless, microhardness measurements such as the Knoop procedure allow discriminating different erosive potentials of various substances on dental hard tissue, even after short exposures (3 min) to acidic agents [27] [25]. In other studies, immersion periods of at least 20 min were chosen to investigate the impact on surface hard-ness [28] [29] [30] [23,26,27]. By means of the indentations on enamel surfaces detection of enamel abrasion is also possible by calculating the depth of the indentations.…”
mentioning
confidence: 99%